MEASURING THE QUALITY OF HIGHER EDUCATION SERVICES DURING THE COVID-19 PANDEMIC: A CASE STUDY OF UNIVERSITAS MURIA KUDUS - Muhkhammat Sahrul Gunawan, Dian Erliana Febriyanti, Rangga Primadasa (Universitas Muria Kudus, 2021)
The spread of Covid-19 led to changes in Higher Education services at Universitas Muria Kudus, where the learning system was carried out online. Servperf is a method for measuring the performance of performance-based service quality. This method is used in this study, where five dimensions of service quality, namely tangible, reliability, responsiveness, assurance, and empathy are used as the basis. The literature review was conducted to obtain 15 indicators. From the results of distributing questionnaires based on these 15 indicators, 118 respondents were students of Universitas Muria Kudus. From the tangible dimensions, the average score is 3, the average reliability dimension score is 3.358757, the Responsiveness dimension has an average score of 3.180791, The Assurance dimension has an average score of 3.217514, and the Empathy dimension has an average score of 2.988701. Whereas the highest score indicator was obtained namely the lecturer workforce was able to communicate and present the material well in online learning with an average score of 3.51. Meanwhile, the lowest indicators are indicators namely Ease of access and internet connection during online learning and the learning process that is easy to understand by students during online learning with the same average score of 2.67.